2017
DOI: 10.5603/gp.a2017.0006
|View full text |Cite
|
Sign up to set email alerts
|

Current views on fetal surgical treatment of myelomeningocele — the Management of Myelomeningocele Study (MOMS) trial and Polish clinical experience

Abstract: Myelomeningocele (MMC) constitutes the most common congenital defect of the central nervous system, with no satisfactory alternative to the postnatal treatment. Prenatal repair of MMC is aimed at protecting from a Chiari type II malformation. The main goal of fetal MMC repair is to improve the development and quality of life in children with a Chiari type II malformation. The Management of Myelomeningocele Study (MOMS), which was published in 2011, confirmed the effectiveness of prenatal surgery. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The Fetal Center at Vanderbilt reported a mean GA of 34.4 ± 3.1 weeks when comparing the MOMS cohort to their post-MOMS cohort [9]. A clinical center in Poland recently published data on their fMMC repair outcomes: 18.3% of their cases reached a GA of 37 weeks (vs. 35.8% in our study population) [10].…”
Section: Discussionmentioning
confidence: 64%
“…The Fetal Center at Vanderbilt reported a mean GA of 34.4 ± 3.1 weeks when comparing the MOMS cohort to their post-MOMS cohort [9]. A clinical center in Poland recently published data on their fMMC repair outcomes: 18.3% of their cases reached a GA of 37 weeks (vs. 35.8% in our study population) [10].…”
Section: Discussionmentioning
confidence: 64%
“…The results of these studies were reported as short term observational studies of cohort groups. The comparison of qualification criteria and surgical protocols remain unanimous [5,12,14,19]. Whereas long-term observation of childhood development after fMMC repair was assessed only in the CHOP study [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…[4]. The Polish team has reported equivalent results as the MOMS trial [30,31]. We matched each child from the OSBAR group with a child from the NSBAR group of the same MMC level and comparable age.…”
Section: Patient Inclusionmentioning
confidence: 99%